1997
DOI: 10.1007/bf01808877
|View full text |Cite
|
Sign up to set email alerts
|

Angiographically unrecognized microaneurysms: Intraoperative observation and operative technique

Abstract: Twenty operated cases of angiographically unrecognized microaneurysm (AUM) have been analysed with special reference to intra-operative observations and clipping-technique. Among the patients with intracranial aneurysms that the authors' facility has operated upon, the incidence of asymptomatic incidental AUM that was 2 mm or smaller amounted to 3.7%. Thirteen cases of AUM were found on the middle cerebral artery; four AUMs arose from the M1 portion, four from the bifurcation, and five from the second bifurcat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The phenomenon of angiographically occult additional aneurysms found during surgery of symptomatic aneurysms is well known in the surgical literature: Yaşargil 6 found, in his series of 1012 symptomatic aneurysms, 377 additional aneurysms, of which 169 (12.2% of all aneurysms) were 2 mm or smaller. Karasawa et al 5 and Inamasu et al 4 reported an incidence of 3.7% and 4.9% of angiographically occult microaneurysms of 2 mm or smaller. If technically possible, these microaneurysms were clipped or wrapped to prevent their growth and rupture.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The phenomenon of angiographically occult additional aneurysms found during surgery of symptomatic aneurysms is well known in the surgical literature: Yaşargil 6 found, in his series of 1012 symptomatic aneurysms, 377 additional aneurysms, of which 169 (12.2% of all aneurysms) were 2 mm or smaller. Karasawa et al 5 and Inamasu et al 4 reported an incidence of 3.7% and 4.9% of angiographically occult microaneurysms of 2 mm or smaller. If technically possible, these microaneurysms were clipped or wrapped to prevent their growth and rupture.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3] However, during surgery of symptomatic aneurysms, additional small angiographic occult aneurysms are commonly found with an incidence of 3.7%-12.2%. [4][5][6] Most neurosurgeons clip or wrap these additional microaneurysms to prevent their growth and rupture. Because the operative view during surgical exploration is restricted to part of the cerebral vasculature, it is likely that the incidence of these small additional aneurysms is higher than that reported in surgical series.…”
mentioning
confidence: 99%
“…Microaneurysms ( Figure 1B ) are IAs with diameters smaller than 2 mm. 5 Most microaneurysms are chronic hypertension related, also known as Charcot-Bouchard aneurysms. They often occur in blood vessels smaller than 0.3 mm and prone to the microvessels in the basal ganglia.…”
Section: Different Types Of Iasmentioning
confidence: 99%
“…This incidence was comparable to two previously reported case series. 6,9 We included only patients with AO aneurysms with preoperative digital subtraction angiography (DSA); had we included patients with AO aneurysms without preoperative DSA, the 28% incidence in this group would have increased the overall incidence of AO aneurysms. AO aneurysms were located most frequently on the MCA and ACoA, and furthermore, there was a significantly higher incidence of AO aneurysms in the MCA and ACoA segments in patients with known MCA and ACoA aneurysms (5.2% vs 1.3% for MCA aneurysms [p < 0.0001] and 2.6% vs 0.6% for ACoA aneurysms [p < 0.0001] in patients with and without known aneurysms there, respectively).…”
Section: Discussionmentioning
confidence: 99%